Antifungal and Zearalenone Inhibitory Activity of Pediococcus pentosaceus Isolated from Dairy Products on Fusarium graminearum - Sellamani, Muthulakshmi; Kalagatur, Naveen K.; Siddaiah, Chandranayaka; Mudili, Venkataramana; Krishna, Kadirvelu; Natarajan, Gopalan; Rao Putcha, Venkata L. (Frontiers in Microbiology, 2016)
The present study was aimed to evaluate the bio-control efficacy of Pediococcus pentosaceus isolated from traditional fermented dairy products originated from India, against the growth and zearalenone (ZEA) production of Fusarium graminearum. Cell free supernatants of P. pentosaceus (PPCS) were prepared and chemical profiling was carried out by GC-MS and MALDI-TOF analysis. Chemical profiling of PPCS evidenced that, the presence of phenolic antioxidants, which are responsible for antifungal activity. Other hand, MALDI-TOF analysis also indicated the presence of antimicrobial peptides. To know the antioxidant potential of PPCS, DPPH free radical scavenging assay was carried out and IC50 value was determined as 32 ± 1.89 µL/mL. The antifungal activity of P. pentosaceus was determined by dual culture overlay technique and zone of inhibition was recorded as 47 ± 2.81%, and antifungal activity of PPCS on F. graminearum was determined by micro-well dilution and scanning electron microscopic techniques. Results showed that, the minimum inhibitory concentration (MIC) was 66 ± 2.18 µL/mL and there was a clear variation in the micromorphology of mycelia treated with MIC value of PPCS compared to untreated control. Further, the mechanism of growth inhibition was revealed by determining the content of ergosterol and reactive oxygen species in PPCS treated samples. The PPCS was effectively decreased the mycelial biomass and ZEA production in a dose dependent manner. The mechanism behind the suppression of ZEA production was studied by reverse transcriptase qPCR analysis of ZEA metabolic pathway genes (PKS4 and PKS13), and results showed that expression levels ZEA metabolic pathway genes were down regulated with increasing concentration of PPCS. The results of the present study were collectively proved the antifungal and ZEA inhibitory activity of PPCS against F. graminearum and it may find a potential application in agriculture and food industry as a natural bio-controlling agent.